PRINCIPLES OF MARRIAGE IN CREATING A SAKINAH FAMILY (THE PROBLEM SIDE OF CHILDREN WHO ARE BORN, CHILDREN WHO ARE NOT FORBIDDEN, TRUE AND UNTRUE JIMAS) - Ridwan; Jumni Neli (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The rising divorce rate, issues surrounding the legal status of children born out of wedlock, and the limited understanding of proper jimak (sexual relations) indicate a gap between the principles of Islamic marriage and socio-legal practices in Indonesia. This study aims to examine the principles of Islamic marriage in realizing a sakinah (harmonious) family, focusing on the status of children, the ethical understanding of jimak, and the validity of marital relations. This research employs a normative-empirical qualitative approach through a literature review of Islamic jurisprudence (fiqh) and positive legal regulations such as the Marriage Law, the Compilation of Islamic Law (KHI), and the Law on Sexual Violence Crimes (UU TPKS). The findings reveal that the principles of Islamic marriage include the validity of the marriage contract (akad), the protection of children’s rights, and sexual relations based on mutual consent. The study also identifies a lack of comprehensive understanding regarding ethical and lawful jimak, as well as the persistence of stigma against children born out of wedlock, despite Constitutional Court rulings and protective provisions within the UU TPKS.